Belize : 2010 Article IV Consultation-Staff Report; Informational Annex; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Belize. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The economy of Belize in recent years has been vulnerable to adverse shocks owing to its weak external position, policy rigidities, and reduced access to external financing. Executive Directors commended the authorities for their prudent macroeconomic management during the crisis. Directors emphasized the need for fiscal consolidation strategy, and stressed the need to strengthen the banking system. They supported plans to improve public financial management and tax administration. They welcomed monetary policy framework, liquidity management, and development plan policies, and offered expert assistance as well.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet